A case report of spontaneous coronary artery dissection complicated by stent fracture. Issue 35 (August 2019) - Gao, Hanxiang; Hu, Ye; Li, Qi; Yao, Suyu; Zhang, Zheng; Bai, Ming
Abstract: Rationale: Spontaneous coronary artery dissection (SCAD) is a rare, complex disease, and nowadays poorly understood. The overall incidence of SCAD ranges from 0.28% to 1.1% in angiographic studies. Therefore, the true incidence of SCAD is most likely underestimated due to asymptomatic or sudden cardiac death before diagnosis. Stent fracture (SF) is a multifactorial issue. Longer vessel remodeled by 2 stents can be more prone to have SF due to higher radial force. Patient concerns: In this paper we report a 48-year-old man with chest pain for 2 years. Diagnoses: Elective coronary angiography revealed a linear dissection in obtuse marginal branch (OM). Interventions: He underwent percutaneous coronary intervention (PCI) with the guidance of intravascular ultrasound (IVUS). Outcomes: Then SF was revealed 9 months later. Lessons: This is the first case report of SF after coronary intervention therapy in SCAD patients.